Non-invasive and husbandry treatment in a singular post-ovulatory egg stasis on an Asian water monitor (Varanus salvator) - Puveanthan Nagappan Govendan; Zefanya Christiani; Michael Nadhor Nainggolan; Slamet Raharjo (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2020)
Asian water monitor (Varanus salvator) is among the largest species of monitor lizards kept in captivity due to the elegancy and character of the species. Captive breeding projects of monitor lizards are not common among reptile keepers. A two years old female V. salvator was presented with complains of anorexic and distended abdomen. No record of copulation or egg deposition was noticed from the particular specimen. Radiography confirmed a post-ovulatory egg-stasis (POES) occurring in the coelomic cavity. Fluid therapy and husbandry improvement was indicated as treatments. Oviposition of the POES was noticed 4 days after treatment. Young monitors could be prone to have less quantity of eggs but larger in size